Manejo do nitrogênio na cultura do melão - Fogaça, Marco Aurelio de Freitas (2007)
The goal of this work was to determine the N requirements of the muskmelon crop and adjusting a method for diagnosis of the plant nutritional status, for estimations of fertilization rates to be used during growth and development of this crop. The experiment was carried out at Departamento de Fitotecnia - UFSM, inside a 500m2 screenhouse. Muskmelon plantlets, hybrid Magelan, were planted at September 30th, 2004, in 4.5dm3 plastic bags containing a commercial substrate. Plant density was 3.3 plants m-2. Water and nutrients were supplied by fertigation. Treatments were five nutrient solutions with N concentrations (NO3 - /NH4 + ) of 8 (T1), 11 (T2), 14 (T3), 17 (T4) and 20mmol.L-1 (T5). The other nutrients were supplied at standard concentrations of 0.9 H2PO4 - ; 2.25 SO4 -- ; 10.0 Ca++; 6.0 K+ and 5.0mmol.L-1 Mg++, with micronutrients. Four plants were weekly harvested from 33 to 99 days after planting (DAP) to determine dry mass (DM), number of fruits (NF), leaf area index (LAI) and N content in tissues. Ripe fruits were harvested at the peduncle abscission stage and fresh weight, flesh firmness, fraction of flesh, skin, mucilage and seeds, titratable acidity and soluble solids were determined. The N content in leaf, stem, petiole and fruit tissues was determined by the Kjeldahl method. The vegetative and total dry mass, leaf area, number and fruit yield increased linearly by effect of treatments. For fruit quality variables, only the titratable acidity decreased by increasing N concentrations. The N dilution was observed during growth of tissues upon all treatments and data fitted the potential model %N = aMS-b described in the literature. The N critical dilution curve was adjusted, with values of 5.16 and 0.63 for model coefficients a and b, respectively. It was concluded that N affects the yield of the crop and can be supplied at rates estimated from the critical dilution curve until fruit setting was attained. After this stage, N fertilization rates can be adjusted in order to avoid any restrictions in the leaf area growth.